Swachhata Hi Seva: Transforming Public Health, Environmental Sustainability, and Water Stewardship Through Community Engagement - Jitender Kumar Saini; Gaurav Singh; S.S. Kerimani (International Journal of Environmental Planning and Development Architecture, 2026)
Swachhata (cleanliness) is not merely a hygiene practice but a foundational driver of public health, environmental resilience, and sustainable development. Recognizing its multidimensional importance, this research critically examines the “Swachhata Hi Seva” campaign as a transformative, community-led movement that elevates cleanliness from an individual responsibility to a collective civic duty and social commitment. The study highlights how the campaign mobilizes diverse community groups, institutions, and local governance structures to actively participate in systematic cleanliness activities that contribute to long-term social and environmental well-being. Adopting a mixed-methods approach, including structured surveys, case studies, government data analysis, and the development of a dedicated water stewardship framework, the study evaluates how Swachhata initiatives influence behavioral change, environmental outcomes, and water resource management. This comprehensive methodology enables a deeper understanding of the interconnected impacts of cleanliness on sanitation, public health, and local ecosystems. The findings reveal that community participation in Swachhata activities significantly enhances sanitation practices, reduces environmental pollution, improves public health indicators, and strengthens water conservation. These improvements are achieved through increased recycling, enhanced groundwater recharge efforts, better wastewater handling, and active community engagement in local water quality monitoring. The research also demonstrates that embedding cleanliness in routine community behavior fosters a culture of environmental responsibility that extends beyond campaign periods. Additionally, the study highlights measurable socioeconomic gains, including reduced public expenditure on waste management, improved efficiency of sanitation services, and strengthened community water security. These outcomes underscore how behavior-centric cleanliness campaigns can evolve into scalable and replicable models for environmentally sustainable development in both urban and rural contexts. By positioning cleanliness as a collective service ethos, Swachhata Hi Seva emerges as a powerful and inclusive framework capable of accelerating national development priorities. The study concludes with actionable policy recommendations, reinforcing Swachhata as a strategic entry point for holistic development at both national and global levels
Keywords: Environment; and waste management; community; sustainable development; swachhata